Integrating Higher Education and Non Formal Education: A Collaborative Model for Sustainable Community Development - Janur Wulan, Dwi; Rahmat Pramudia, Joni; S Ardiwinata, Jajat (Cirebon Annual Multidiciplinary International Conference (CAMIC), 2026)
The integration of higher education and non-formal education represents a strategic approach to advancing sustainable community development, particularly in expanding lifelong learning opportunities and strengthening community capacity. However, collaboration between these two sectors often remains fragmented, short-term, and insufficiently structured within an equitable and sustainable partnership framework. In response to this challenge, this study aims to examine and formulate a collaborative model that integrates higher education and non-formal education in support of sustainable community development. This study employed a qualitative case study design conducted at a non-formal education institution, PKBM Ibun, located in Bandung Regency, Indonesia. Data were collected through in-depth interviews, participatory observation, and document analysis involving representatives from higher education institutions, non-formal education practitioners, and community members. The data were analyzed using thematic analysis to identify patterns of collaboration, implementation mechanisms, stakeholder roles, and contributions to social, educational, and economic sustainability. The findings indicate that effective collaboration is characterized by dialogical partnerships, the integration of academic knowledge with local practices, and active community engagement throughout all stages of program implementation. The resulting collaborative model not only enhances community learning capacity but also strengthens social participation and the sustainability of local development initiatives. The novelty of this study lies in the development of an integrative collaborative model that positions higher education and non-formal education as equal partners within a social learning ecosystem, contributing to the achievement of the Sustainable Development Goals.